Evaluation of oil palm site suitability using analytical hierarchy processing developed index and geographical information system application at Kg. Beratok and Kg. Tapah Samarahan - Kho, Ai Ling (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Problem of unsuitable land use and irregular development of agricultural areas result in the reduction in cultivation. Hence, appropriate method of land suitability evaluation can provide sustainable management agricultural lands for policy maker for a project planning and managemend In this study, evaluation on the oil palm suitability is conducted by adopting the existing oil palm index formulated by multi criteria evaluation method in GIS and Analytical Hierarchy Processing (AHP) and Pairwise Comparison method for factor ranking and weighting. Seven environmental factors affecting the suitability of oil palm growth considered in the oil palm index are soil texture, slope, soil drainage, soil depth, groundwater table depth, total organic carbon, and water deficit. Field measurement was conducted using simple random sampling method at Kg. Beratok and Kg. Tapah .. The soil structures were studied and the samples were analyzed in the laboratory. Result of studies obtained through the ground reference verification and analysis were inserted into the linear combination method. Inverse Distance Weighted (lOW) interpolation method in the ArcGlS were use for generating the spatial information regarding the site suitability for oil palm plantation as to predict the cell values for location which were lack of sampling points due to the limitation for inaccessibility. The results indicate that the Oil Palm Suitability map generated had shown majority of the study area fell into moderate suitable whereas, about 2587.0 hectares (73.8%) of the land was moderately suitable, while 383.6 hectares (11.0%) ~s suitable and 534.3 hectares (15.2%) is unsuitable for the oil palm planting respectively. The results indicated that the application multi-factor evaluation using AHP in identifying sites suitability for plantation could provide a superior database and guide map for decision makers to make a precise judgment for better output. Thus result in project cost saving in terms of extra intensive inputs and promising a higher productivity of oil palm yield in return.